2006
DOI: 10.1213/01.ane.0000197611.89464.98
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Piroxicam for Postoperative Analgesia: Preoperative Versus Postoperative Administration: A Randomized, Double-Blind Study

Abstract: Nonsteroidal antiinflammatory drugs have been used to obtain preemptive analgesia. We investigated, in this randomized, double-blind study, whether sublingual (s.l.) piroxicam given before was more effective than that given after surgery. Fifty-two patients scheduled for laparoscopic bilateral inguinal hernia repair under general anesthesia were enrolled. Group PRE (25 patients) received 40 mg of piroxicam s.l. 2 h before surgery and a placebo 10 min after surgery. Group POST (27 patients) were treated with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
1
18
0
2
Order By: Relevance
“…Studies have shown that surgical wound infiltration with local anesthetics is effective to control acute postoperative pain in different procedures, because it decreases pain and opioid consumption 2,13,14 . Wound infiltration with local anesthetics has also been recommended to decrease perioperative opioid consumption 7 . In our study, pain intensity was evaluated by VAS, established method in the literature, since pain intensity described by patients has been referred as one of the most reliable measures to estimate analgesic treatment effectiveness 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that surgical wound infiltration with local anesthetics is effective to control acute postoperative pain in different procedures, because it decreases pain and opioid consumption 2,13,14 . Wound infiltration with local anesthetics has also been recommended to decrease perioperative opioid consumption 7 . In our study, pain intensity was evaluated by VAS, established method in the literature, since pain intensity described by patients has been referred as one of the most reliable measures to estimate analgesic treatment effectiveness 9 .…”
Section: Discussionmentioning
confidence: 99%
“…However, its effectiveness as compared to conventional regimens to manage postoperative acute pain is still controversial. Some studies could not show beneficial effects with any preemptive drug, although others have shown preemptive effect only with non-steroid anti-inflammatory drugs (NSAIDS), local anesthetics and other drugs [2][3][4][5][6][7] . Local wound infiltration with local anesthetics has been recommended to decrease perioperative opioid consumption and postoperative pain, however there is a study which could not show differences in postoperative pain intensity with pre or postoperative infiltration with bupivacaína or lidocaine 2,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…A total of three RCTs yielded three comparisons, in which the oxicams class of NSAIDs were administered preoperatively, were incorporated in the metaanalyses, studying 172 adult patients (85 received oxicams, 87 received placebo; Table 1; Table 2, notes 13,14) (Akca et al, 2004;Gramke et al, 2006;Mowafi et al, 2011). The meta-analysed oxicams were lornoxicam (1 study, medium dose; Mowafi et al, 2011), piroxicam (1 study, high dose; Gramke et al, 2006) and tenoxicam (1 study, medium dose; Akca et al, 2004).…”
Section: Oxicamsmentioning
confidence: 99%
“…The meta-analysed oxicams were lornoxicam (1 study, medium dose; Mowafi et al, 2011), piroxicam (1 study, high dose; Gramke et al, 2006) and tenoxicam (1 study, medium dose; Akca et al, 2004).…”
Section: Oxicamsmentioning
confidence: 99%
“…The variable patient characteristics and timing of preemptive analgesia in relation to surgical stimuli might require particular treatments for each patient. Thus, for practitioners who aspire to apply the advantage of preemptive analgesia with NSAIDs, following the concept of evidence-based medicine, it is necessary to have results that support the relevant preemptive analgesic effect in clinical investigations [1,[4][5][6].…”
mentioning
confidence: 99%